Partitioning of trace elements and metals between quasi-ultrafine, accumulation and coarse aerosols in indoor and outdoor air in schools. (April 2015) - Viana, M.; Rivas, I.; Querol, X.; Alastuey, A.; Álvarez-Pedrerol, M.; Bouso, L.; Sioutas, C.; Sunyer, J.
Abstract: Particle size distribution patterns of trace elements and metals across three size fractions (<0.25 μm, quasi-ultrafine particles, q-UF; 0.25–2.5 μm, accumulation particles; 2.5–10 μm, coarse particles) were analysed in indoor and outdoor air at 39 primary schools across Barcelona (Spain). Special attention was paid to emission sources in each particle size range. Results evidenced the presence in q-UF particles of high proportions of elements typically found in coarse PM (Ca, Al, Fe, Mn or Na), as well as several potentially health-hazardous metals (Mn, Cu, Sn, V, Pb). Modal shifts (e.g., from accumulation to coarse or q-UF particles) were detected when particles infiltrated indoors, mainly for secondary inorganic aerosols. Our results indicate that the location of schools in heavily trafficked areas increases the abundance of q-UF particles, which infiltrate indoors quite effectively, and thus may impact children exposure to these health-hazardous particles. Highlights: Quasi-ultrafine particles (q-UF) are measured indoors and outdoors in 39 schools. Particle size distribution patterns of trace elements and metals are described. High proportions of typically coarse elements are found in q-UF particles. Potentially health-hazardous metals are found in q-UF in indoor air. The location of schools in trafficked areas increases children exposure to q-UF.